THE RELATIONSHIP BETWEEN THE NUMERICAL ABILITY, MATHEMATICAL CONNECTIONS ABILITY, AND CLASSMATES LEARNING INTERACTION WITH MATH LEARNING OUTCOMES OF SMAN 2 BANGUNTAPAN - Ma’rifatun Khoiriyah; Sunaryo Sunaryo (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
Many factors are associated with mathematics learning outcomes. Numerical ability, mathematical connections ability and classmates learning interactions were related to student learning outcomes. Therefore, this study aimed to determine whether there is a relationship between the numerical ability, mathematical connections ability, and classmates learning interactions with math learning outcomes of students class XI IPA in even semester of SMAN 2 Banguntapan in Academic Year 2015/2016. The population in this study were students of class XI IPA at SMAN 2 Banguntapan Bantul in Academic Year 2015/2016 consisting of four classes, are class XI IPA 1, XI IPA 2 IPA 3 XI, and XI IPA 4 by the total of students by 100 students. Class XI IPA 3 was selected as a sample class using random sampling techniques, consisting of 27 students. Data collection techniques are done with the test method to determine the numerical ability, mathematical connections ability, and mathematics learning outcomes, the questionnaire method to determine the classmates learning interactions. To test instruments using validity, reliability and power difference. After the data collected, analyze prerequisite tests including normality test, independence, and linearity. Data analysis for hypothesis testing using product-moment correlation analysis and multiple linear regression analysis. The results showed that there is a positive and significant correlation between the numerical ability, mathematical connections ability, and classmates learning interactions with math learning outcomes by  and , so . Multiple correlation coefficient of the regression equation =29,3747+0,6820 X +0,2357 X -0,3449 X3. The relative contribution of variable X  by 70.2356%, of the variable X2 by 11.6737% and of the variable X3 by 18.0907%. The coefficient of multiple determination by 0.3026 with the effective contribution of variable X  by 21.25667%, of variable X  by 3.53303% and of the variable X3 by 5.47512%.